Motivasi Pengambilan Keputusan Generasi Milenial dalam Memilih Pekerjaan Kreatif di Kota Padang - Laura Sari Ramadhani (Universitas Merdeka Malang, 2023)
Popular culture leads to the creation of culture that is produced and presented in large quantities with the help of production, distribution and mass access technologies so that it is easily accessible to the public. This research aims to answer the motivation of the millennial generation in choosing creative jobs and explain that these jobs are a sign of the existence of popular culture in the city of Padang. This research uses a qualitative method with a phenomenological approach with snowball sampling. Data was collected through literature study, observation, interviews and documentation. Theresearch results illustrate the motivation of the millennial generation in choosing creative work in the form of ideals, talents and means of self-development. In a broader scope there is economic motivation and opportunities to develop in the future with the work they are involved in. Their behavior that prioritizes balance between work and doing other things outside of work (work-life balance), being a role model and reflection, and maintaining popularity is the behavior that gives birth to and maintains popular culture.